(untitled) (Indian Journal of Arid Horticulture, 2025)
Black cumin (Nigella sativa L.) is a valuable spice and medicinal crop however, in the semi-arid Northern Telangana Zone, there is a lack of comprehensive evaluation of improved black cumin varieties under dryland conditions. This study aimed to assess the performance of five varieties AN-1, AN-20, NS-32, NS-44, and a local check during the Rabi season of 2024-25 at the Horticultural Research Station, Adilabad. Significant variation was observed among the varieties for plant height, number of branches, capsules per plant, seeds per capsule, 1000-seed weight, and seed yield. AN-20 recorded the highest seed yield (1258.33 kg/ha), followed by AN-1 and NS-32, while the local check showed the lowest performance. These findings suggest that AN-20 and AN-1 are well-adapted to semi-arid dryland conditions and hold promise for commercial cultivation in the Northern Telangana region.